2014
DOI: 10.1186/1471-244x-14-104
|View full text |Cite|
|
Sign up to set email alerts
|

Neurobehavioral consequences of chronic intrauterine opioid exposure in infants and preschool children: a systematic review and meta-analysis

Abstract: BackgroundIt is assumed within the accumulated literature that children born of pregnant opioid dependent mothers have impaired neurobehavioral function as a consequence of chronic intrauterine opioid use.MethodsQuantitative and systematic review of the literature on the consequences of chronic maternal opioid use during pregnancy on neurobehavioral function of children was conducted using the Meta-analysis of Observational Studies in Epidemiology (MOOSE) and the Preferred Reporting Items for Systematic Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 68 publications
(84 reference statements)
3
71
1
6
Order By: Relevance
“…In addition, a small study found that methadone-exposed children had trending lower IQ scores and greater reports of anxiety, aggression and rejection compared with control children [47]. There have been other studies, however, that show little to no significant cognitive differences between babies exposed to opiates and control subjects later in life [48,49], which suggests that other factors (not controlled for in these studies) likely influence the risk of behavioural or cognitive deficits associated with prenatal opiate exposure. Interestingly, children exposed to heroin prenatally that were then adopted into a controlled household at a young age experienced behavioural deficits associated with ADHD at much lower rates [46].…”
Section: (A) Prenatal Exposure To Opiatesmentioning
confidence: 79%
“…In addition, a small study found that methadone-exposed children had trending lower IQ scores and greater reports of anxiety, aggression and rejection compared with control children [47]. There have been other studies, however, that show little to no significant cognitive differences between babies exposed to opiates and control subjects later in life [48,49], which suggests that other factors (not controlled for in these studies) likely influence the risk of behavioural or cognitive deficits associated with prenatal opiate exposure. Interestingly, children exposed to heroin prenatally that were then adopted into a controlled household at a young age experienced behavioural deficits associated with ADHD at much lower rates [46].…”
Section: (A) Prenatal Exposure To Opiatesmentioning
confidence: 79%
“…Kurita et al [24] established that one-third of opioid-treated patients with cancer had possible or definite cognitive dysfunction. In contrast, Baldacchino et al [25] found that children with Schmidt chronic intrauterine exposure to opioids experienced no significant impairment in neurobehavioral outcomes when compared to non-exposed peers. These findings indicate that chronic opioid exposure is not automatically associated with impairments in neurobehavioral outcomes.…”
Section: Introductionmentioning
confidence: 93%
“…70 A recent systematic review and meta-analysis on neurobehavioral consequences of in utero opioid exposure in infants and preschool children showed no significant impairments for behavioral, psychomotor or cognitive outcomes in exposed children compared to non-exposed controls. 71 However, an error in data entry was uncovered after publication, and in the repeated, corrected analyses significant impairments with small effect sizes were found in opioid-exposed children for all the included neurobehavioral outcomes. 72 A national, population-based cohort of 38 children born to mothers included in OMT and 36 comparison children from a low-risk population have been followed from birth in a Norwegian, longitudinal study.…”
Section: Prenatal Opioid Exposure and Neuropsychological Impairmentsmentioning
confidence: 99%